Assessment of the skin tissue structure using an ultrasonic diagnostic imaging device in patients undergoing open surgery. Issue 6 (29th May 2019) - Oohashi, Fumiya; Suto, Takashi; Matsui, Hiroki; Shirabe, Ken; Uchida, Yoko
Abstract: Background: Perioperative skin injury is a major issue; therefore, several preventative measures have been developed. However, no previous studies have visualized the effects of stromal edema caused by surgical invasion of skin tissue, and therefore, the details remain unknown. We used an ultrasonic diagnostic imaging device to clarify changes in the skin tissue structure of patients after open surgery. Materials and Methods: Twenty subjects who underwent open hepatectomy were enrolled. We selected the lateral abdomen, upper arms, and lower legs as ultrasonic imaging measurement sites. We performed measurements on the day before surgery and on postoperative days 1, 3, and 5. We calculated the epidermal/dermal tissue thickness, subcutaneous tissue thickness, and skin tissue thickness. We performed a one‐way analysis of variance with repeated measurements for each of the postoperatively measured values on the basis of the preoperative values. Significantly different variables were subjected to the Bonferroni method. We evaluated ultrasonic imaging findings and skin injury. Results: Epidermal/dermal tissue thickness at all measurement sites exhibited sustained thickening on postoperative day 5 compared to that preoperatively. The lateral abdomen exhibited thickening of the subcutaneous tissue and skin tissue on postoperative day 1. In addition, increased echogenicity, increased opacity of the layer structure, and a cobblestone appearance occurred during the postoperative course. Postoperatively, 80% of subjects exhibited skin injury. Conclusion: We evaluated the effects of surgical invasion on skin tissue over time. Continual observation and protective skincare are necessary near the surgical wound, where significant invasiveness occurs. Prevention of skin injury due to skin tissue thickening requires further study.